Analysis and Design of Enterprise Architecture in The Implementation of Digital Transformation at Village Tourism of Kampung Patin Kampar Regency using TOGAF - Firmananda, Fahmi Iqbal; Ependi, Zulfan; Adeswastoto, Hanantatur (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The development of information technology helps the community, entrepreneurs and MSMEs. This research was conducted in Kampung Patin, Kampar Regency. This research aims to create an Enterprise Architecture (EA) TOGAF design for MSMEs in Kampung Patin, we all know this digital transformation is useful in increasing the business value of the surrounding economy. there is a special implementation in utilizing this role, building financial applications, raw material stock applications because these MSMEs are able to produce 34,000 tons to 45,000 tons of catfish every month. The processing of catfish is like regional souvenirs, namely: catfish meatballs, catfish nuggets, catfish batagor, catfish fillets, and catfish skin crackers. innovation like this alone is not enough to require technology and digital transformation in running a business and promoting processed catfish. the results of the study were designed in the form of an enterprise architecture blueprint for UMKM Kampung Patin as an internal guidebookincrease the effectiveness and efficiency of digital transformation in these MSMEs